Let it go. “Déjalo ir” or “Suéltalo”? Audiovisual translation of songs, machine translation and post-editing in the foreign language classroom - Jordán Enamorado, Miguel Ángel; Ricart Vayá, Alicia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we offer a teaching methodology to improve the communicative competence and digital skills of foreign language students through the audiovisual translation of songs by means of machine translation tools followed by the post-editing of the texts. This methodology has been implemented satisfactorily in the subject English 3 (C 1 level) of the degrees of English Studies and Translation and Interlinguistic Mediation of the University of Valencia.